Design, analysis and fabricate of foldable and adjustable desk / Muhammad Ammar Amsyar Azran and Mohd Fadzli Ismail - Azran, Muhammad Ammar Amsyar; Ismail, Mohd Fadzli (School of Mechanical Engineering, 2022)
Foldable and adjustable desks are mostly used for offices and education institutes in daily life to carry on indoor employment such as typing and writing. Foldable and adjustable desks come with the ability to fold which can save space and the height adjustable properties suitable for all ages. The ability to convert into a briefcase and open to be a table makes it foldable. The steps must be followed to convert it into a table. Firstly, unlock the two buckles and open the half part of the tabletop 180 degrees. Then for the leg part, open all leg to 90 degrees and adjust the height of the table either want it tall or short. Lastly, rotate the table 180 degrees. The result of fabrication is that certain parts cannot work because the table cannot reach the maximum height and the tabletop can break if try to reach it. Lastly, the conclusion is the objective has been achieved and this product needs more improvement in the future